(untitled) (Journal of Hama University, 2025)
This research aimed to measure the efficiency of the International Bank for Trade and Finance and the possibility of analyzing it during the period 2012-2022, using the Data Envelopment Analysis (DEA) model (input orientation model) as one of the relatively modern statistical analysis methods. To achieve this, it relied on studying and analyzing some of the most important budget items of the bank under study, and knowing whether it enjoys relative efficiency or not, especially in light of the competition with private banks that have acquired a large share of the volume of Syrian banking business. Based on the above, it was necessary to study the efficiency of the performance of the International Bank for Trade and Finance; to know the extent of its impact on all variables, using the input orientation model using the fixed volume returns model and the variable volume returns model; to find efficiency indicators according to the aforementioned model. The debit interest and employee expenses were also used as inputs to the model, while profits were used as an output to the model. Many conclusions were reached, the most important of which is: The International Bank for Trade and Finance was relatively efficient in 2021 only